Effects of combinations of pre-operative submucosal methylprednisolone with different post-operative analgesic agents in pain control following surgical removal of impacted third molar / Nurhalim Ahmad - Nurhalim, Ahmad (2019)
Introduction : Mandibular third molar is the most frequently impacted tooth and surgical removal of impacted mandibular third molar is the most common performed surgical intervention in dentistry. As any other surgeries, the procedure possesses risks of complications. The common sequelae of mandibular third molar surgery are post operative pain, facial swelling and trismus. These occur as a result of natural inflammatory process which often affect patients’ ability to perform their daily activities thus, compromise their quality of life. Attempts to reduce the post-operative complications after third molar surgery have been made using variety of anti-inflammatory drugs and the usage corticosteroids has been extensively studied. Objective : The objective of this study is to evaluate the effects of combinations pre-operative submucosal methylprednisolone with different post-operative analgesics in pain control following surgical removal of impacted third molars. Methods : This study is a prospective randomised clinical trial performed on 60 subjects by one single operator. Patients were divided randomly into 3 groups. Group 1 received pre-operative submucosal methylprednisolone with post-operative ibuprofen, Group 2 received preoperative submucosal with post-operative paracetamol whereas Group 3 was the control group received only post-operative ibuprofen. Baseline measurement and subsequent assessments were made on post-operative day 1, 2 and 7. Data was analysed with SPSS version 24.0 with p-value set at <0.05 as significant. Result : Post-operative evaluation showed that there was a significant difference between the study and control group on VAS score in post-operative 4, 6, 7 and 8 hours (p-values <0.05). There was no significant difference between the two methylprednisolone groups in VAS score (p-value >0.05). Both methylprednisolone groups showed lower VAS score at post-operative day 2 and 7 although they were not statistically significant (p-value >0.05) as compared to the control group. It was observed that patients in control group also consumed more rescue vi analgesics as compared to methylprednisolone groups. Conclusion : Patients given preoperative submucosal injection of 40mg methylprednisolone before surgical removal of impacted third molar did show significant pain control post-operatively. This beneficial effect was seen mostly at day one post-operative.